Rethinking international adoption from a children-focused perspective - Gallego Molinero, Aránzazu (Cuadernos de Trabajo Social, 2013)
This article aims at a non adult-centric reflection about international adoption of Ethiopian children in Spain. From an approach based on children’s rights applied to international adoption, we offer a critical analysis on how these practices do not respond nowadays to the basic principles of best interest of the child, subsidiarity, and adoptability of the children, which are the ruling principles in international rules and national legislation in Spain and Ethiopia.